Prevalence of Cancer-Related Fatigue: A Prospective Observational Study - Reddy, Pradeep K.; Rajkumar, Billakanti; Shrivastava, S.P.; Soumya, Paspula; Divya, Brungi; Anvesh, R.; Bhavani, Bayya Neha; Gouthami, Gouthami; K., Niharika; Bhatnagar, Shweta (South Asian Journal of Cancer, 2025)
Cancer-related fatigue (CRF) reduces quality of life and the activity level of patients with cancer. Data regarding CRF from Indian population are limited. The present study was aimed to understand the prevalence of CRF in Indian patients and its impact on quality of life.This prospective observational study was conducted at SVS Medical College, Telangana, India, for a duration of 6 months. The study included 100 adult patients with cancer receiving treatment at the institute and willing to consent for the study. The patients with brain metastases were excluded as it might impact their ability to complete study procedures. Patients' demographics, disease and treatment details, etc. were collected. Patients were interviewed to assess the level of fatigue using the EORTC QLQ-C30 (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30) scale and the National Comprehensive Cancer Network (NCCN) fatigue intensity scale. The analysis of data was performed using chi-square and analysis of variance tests.In our study of 100 Indian patients (49 males and 51 females), mean age was 43.78 years. Breast cancer and gastric cancer were the most common diagnosis, with 22 patients each. Treatment protocols included radiotherapy in 63 patients and chemotherapy in 37 patients. As per the EORTC QLQ-C30 scale, proportion of patients with normal, mild, moderate, and severe level of fatigue were 9, 15, 44, and 32%, respectively. As per the NCCN scale, proportion of patients with no or mild, moderate, and severe fatigue were 9, 47, and 44%, respectively.Our study suggests that among the Indian patients with CRF, higher proportion of patients have moderate or severe level of fatigue. Appropriate assessment and management of CRF should be considered in the patients for overall management.
Keywords: cancer-related fatigue; chemotherapy; physical activity; pharmacological; radiotherapy; integrative therapies